THE ROLE OF TOPONYMS IN THE ONOMASTIC FIELD OF THE FAIRY TALE - Nazarova Nurjahon Bakhodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides information about the role of toponyms in the text of the fairy tales. Most of the onomastic units mentioned in fairy tales are made up of toponyms, and they reflect the geographical and religious-mystical imagination, living conditions, and social life of the representatives of the English and Uzbek linguistic cultures. In this article main feautures of toponyms in fairy tales are discussed.